Abdurrahman Wahid’s Thought about Democracy in 1974-2001 - Yunitasari, Yessyca; Sugiyanto, Sugiyanto; Swastika, Kayan (JURNAL HISTORICA, 2017)
This study aims to analyze Abdurrahman Wahid’s thought about democracy including what the factors of his idea in realizing democracy. The method used in this study is historical research method. The result showed that because democratic values haven’t run well, so Abdurrahman Wahid want to implement democracy in the domain of social, political, and economic. According to Abdurrahman Wahid, a democratic state when equalized all citizens before the law, upholds sovereignty law, free stating opinion, apply function checks and balance, and give priority to the welfare. The conclusion is thought Abdurrahman Wahid about democracy influenced by the sociocultural, education, and political experience, who good synergy, until formed the idea of democracy. This research is expected to be a reference for the community to apply the values of democracy in order unites the various interests and the diversity of Indonesian peoples. Keywords: Abdurrahman Wahid, political thought, and democracy.